THE IMPACT OF FINANCIAL DEVELOPMENT AND THE INFORMAL ECONOMY ON SUSTAINABLE DEVELOPMENT IN ASEAN - Muhammed, Ismail; Musa, Sulaiman (Bank Indonesia, 2025)
This study examines the interplay among the ASEAN region’s financial development, informal economy, and sustainable development. While financial development is expected to support economic growth, its relationship to sustainability remains ambiguous, particularly in economies with significant informal sectors. Using a panel dataset from 1991 to 2020 across 10 ASEAN countries, the study employs robust econometric techniques, including fixed effects, feasible general least squares methodology, and quantile regression, to assess the direct and indirect effects of financial development and informality on sustainability. Findings reveal that the informal economy positively contributes to sustainable development, likely by providing employment and economic opportunities. However, financial development, measured by a broad money supply and private sector credit, has a negative impact, suggesting that financial resources are not effectively allocated to sustainability-driven sectors. The interaction between financial development and informality further exacerbates sustainability challenges, indicating a misalignment between formal financial mechanisms and informal economic activities. These results highlight the need for policy strategies integrating informal sector dynamics into financial systems, ensuring financial growth translates into broader sustainable development outcomes. Strengthening financial inclusion and directing capital to sustainability-focused initiatives could help bridge the gap between formal finance and the informal economy in ASEAN nations.